A New Variant of the IER3IP1 Gene: The First Case of Microcephaly, Epilepsy, and Diabetes Syndrome 1 from Turkey - Elif Söbü; Gül Demet Kaya Özçora; Elif Yılmaz Güleç; Bahtiyar Şahinoğlu; Feride Tahmiscioğlu Bucak (Galenos Yayincilik, 2024)
Microcephaly, epilepsy and diabetes syndrome 1 (MEDS1) is a rare autosomal recessive disorder caused by defects in the immediate early response 3 interacting protein 1 (IER3IP1) gene. Only nine cases have been described in the literature. MEDS1 manifests as microcephaly with simplified gyral pattern in combination with severe infantile epileptic encephalopathy and early-onset permanent diabetes. A simplified gyral pattern has been described in all cases reported to date. Diagnosis is made by demonstration of specific mutations in the IER3IP1 gene. In this study, we present an additional case of a patient with MEDS1 who was homozygous for the c.53C>T p.(Ala18Val) variant. This case, the first to be reported from Turkey, differs from other cases due to the absence of a typical simplified gyral pattern on early brain magnetic resonance imaging, the late onset of diabetes, and the presence of a new genetic variant. The triad of microcephaly, generalized seizures and permanent neonatal diabetes should prompt screening for mutations in IER3IP1.